2017
DOI: 10.1016/j.jhazmat.2016.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical cell for simultaneous electricity generation and heavy metals recovery from wastewater

Abstract: Additional Information:• This paper was accepted for publication in the journal Journal of Haz-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…metal removal/recovery [99][100][101][102]; and, simultaneous generation of electricity and hydrogen [12,[103][104][105].…”
Section: Semiconductor Materials Applied In Photoelectrocatalytic Wasmentioning
confidence: 99%
See 1 more Smart Citation
“…metal removal/recovery [99][100][101][102]; and, simultaneous generation of electricity and hydrogen [12,[103][104][105].…”
Section: Semiconductor Materials Applied In Photoelectrocatalytic Wasmentioning
confidence: 99%
“…The semiconductor materials that are applied in photoelectrocatalytic treatment of wastewater include photoanodes (n-type) and photocathodes (p-type) if oxidation or reduction is the main process at the interface [84]. Thus, photoelectrocatalysis is developed in such wastewater treatment field as: organic compounds oxidation [92,93]; inorganic ions reduction [94,95]; disinfection [96][97][98]; metal removal/recovery [99][100][101][102]; and, simultaneous generation of electricity and hydrogen [12,[103][104][105].…”
Section: Single Semiconductor Photoelectrode Materialsmentioning
confidence: 99%
“…The photogenerated electrons are injected, as already said, into the host conduction band of titania, which lies at an energy level approximately equal to E 0 = −1.0 V, in an alkaline environment, as it is the case with the S 2− /SO 3 2− electrolyte in the anode compartment. The pH of the Na 2 SO 4 electrolyte in the cathode compartment is around 6; therefore, the corresponding potential of Equation (5) in such an electrolyte is around E 0 = +0.33 V. The difference between these potentials is approximately equal to 1.33 V; therefore, there is sufficient bias to drive electrons from the photoanode to the counter electrode and carry out oxygen reduction. Consequently, the cell is expected to run by itself as a solar cell without any external bias.…”
Section: Resultsmentioning
confidence: 99%
“…PFC is a fuel cell which is based on the photocatalytic oxidation of a sacrificial agent at the photoanode and the reduction of dioxygen at the cathode electrode. PFC then is a photoelectrochemical cell which consists of two electrodes; one anode and one cathode, in contact with an electrolyte [1][2][3][4][5][6][7][8][9][10][11]. The (photo)anode carries a semiconductor photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental sustainability challenge is also growing at a large scale and complexity, resulting in severe environmental impacts including water pollutions. Within this context, the rise of industrialization alongside with the rapid growth of the global population has been intimately linked with a higher generation of wastewater [1][2][3]. The statistical glance from United Nations World Water Assessment Programme (2003) has reported that around 2 million tons of industrial sewage and agricultural waste have been discharged into the water bodies every day.…”
Section: Introductionmentioning
confidence: 99%